2009
DOI: 10.1074/jbc.m809089200
|View full text |Cite
|
Sign up to set email alerts
|

Glycolipid Acquisition by Human Glycolipid Transfer Protein Dramatically Alters Intrinsic Tryptophan Fluorescence

Abstract: Glycolipid transfer proteins (GLTPs) are small, soluble proteins that selectively accelerate the intermembrane transfer of glycolipids. The GLTP fold is conformationally unique among lipid binding/transfer proteins and serves as the prototype and founding member of the new GLTP superfamily. In the present study, changes in human GLTP tryptophan fluorescence, induced by membrane vesicles containing glycolipid, are shown to reflect glycolipid binding when vesicle concentrations are low. Characterization of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(72 citation statements)
references
References 51 publications
6
66
0
Order By: Relevance
“…4C). The near-UV CD signal, originating from environmentally induced optical activity of Phe, Tyr, and Trp, is largely unaffected by incubation with PC vesicles containing glycolipid, consistent with diffraction data showing only subtle changes in tertiary folding as a consequence of glycolipid binding by GLTP (9,10,46). Nonetheless, when the vesicles lack glycolipid, a hint of tertiary change is observed in the near-UV CD signal associated with Tyr and/or Trp, prompting the further study of intrinsic Trp fluorescence in HET-C2.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…4C). The near-UV CD signal, originating from environmentally induced optical activity of Phe, Tyr, and Trp, is largely unaffected by incubation with PC vesicles containing glycolipid, consistent with diffraction data showing only subtle changes in tertiary folding as a consequence of glycolipid binding by GLTP (9,10,46). Nonetheless, when the vesicles lack glycolipid, a hint of tertiary change is observed in the near-UV CD signal associated with Tyr and/or Trp, prompting the further study of intrinsic Trp fluorescence in HET-C2.…”
Section: Discussionsupporting
confidence: 64%
“…6, bottom right). The latter finding was unexpected because ethanol-injected POPC has little effect on GLTP Trp emission intensity (46). The data suggested that interaction of HET-C2 with membrane alters the local environment of Trp 208 either directly or by triggering conformational changes that precede glycolipid uptake.…”
Section: Intrinsic Trp Fluorescence Changes Induced By Membranes Contmentioning
confidence: 48%
See 3 more Smart Citations